A perspective review: Technical study of combining phase contrast magnetic resonance imaging and computational fluid dynamics for blood flow on carotid bifurcation artery - Mohd Azrul Hisham, Mohd Adib; Lim, Sheh Hong; Mohd Shafie, Abdullah; Radhiana, Hassan; Wada, Shigeo (Faculty Mechanical Engineering, UMP, 2020)
Nowadays, the knowledge of precise blood flow patterns in human blood vessels, especially focusing on Carotid Bifurcations Artery (CBA) area by using computational and modern techniques are very important to develop our understanding regarding to human diseases for both essential research and clinical treatment. This paper tends to discuss the progress regarding to the integration between Phase Contrast Magnetic Resonance Imaging (PC-MRI) and Computational Fluid Dynamics (CFD), specifically to the human diseases. We technically define the model geometry reconstruction, review both PC-MRI and CFD methods to create mesh models, obtain boundary conditions, define the governing equations in CFD, define the material properties, and assumptions used in running the CFD simulations. Detailed information on PC-MRI and CFD is provided in tables, such as the MRI setup, software used, CFD model setup, measurement parameter, and summary of the result contribution from each reviewed article. Numerous fusions between PC-MRI and CFD are specified by summarizing the investigation carried out by significant group’s research, reviewing the important outcomes, and discussing the techniques, drawbacks and possibilities for further study. We hope that this perspective analysis will encourage a fusion of PC-MRI and CFD research contributing to continuous advancement of human health with close cooperation and collaboration among clinicians and engineers.